Evaluation of geomembrane UV degradation using melt flow index and oxidative induction time tests - Lodi, P. C. [UNESP]; Bueno, B. S.; Vilar, O. M. (Zhejiang Univ Press, 2008)
Many factors such as the sunlight, intensity of radiation, temperature, and moisture may influence the degradation process of geosynthetics. UV stabilizers are used especially in polyolefin geomembrane to prevent the degradation process. In these geomembranes the service lifetime is initially governed by the consumption of antioxidants. Tests like MFI and OIT are a alternative to detect the oxidative degradation in polyolefins. This article evaluates HDPE geomembrane degradation after UV exposure through the results of MFI and OIT tests. Two kinds of geomembranes were evaluated: a black and smooth (0.8, 1.0, 1.5, 2.5 mm) and a white and textured (1.0 mm). MFI test showed some levels of superficial degradation (crosslink) in HDPE geomembrane.
Keywords: geomembranes; UV exposure; MFI and OIT tests